Cost‐effectiveness of a collaborative dementia care management—Results of a cluster‐randomized controlled trial. Issue 10 (10th August 2019) - Michalowsky, Bernhard; Xie, Feng; Eichler, Tilly; Hertel, Johannes; Kaczynski, Anika; Kilimann, Ingo; Teipel, Stefan; Wucherer, Diana; Zwingmann, Ina; Thyrian, Jochen René; Hoffmann, Wolfgang
Abstract: Introduction: The purpose of this study was to determine the cost‐effectiveness of collaborative dementia care management (DCM). Methods: The cost‐effectiveness analysis was based on the data of 444 patients of a cluster‐randomized, controlled trial, conceptualized to evaluate a collaborative DCM that aimed to optimize treatment and care in dementia. Health‐care resource use, costs, quality‐adjusted life years (QALYs), and incremental cost per QALY gained were measured over a 24‐month time horizon. Results: DCM increased QALYs (+0.05) and decreased costs (−569€) due to a lower hospitalization and a delayed institutionalization (7 months) compared with usual care. The probability of DCM being cost‐effective was 88% at willingness‐to‐pay thresholds of 40, 000€ per QALY gained and higher in patients living alone compared to those not living alone (96% vs. 26%). Discussion: DCM is likely to be a cost‐effective strategy in treating dementia and thus beneficial for public health‐care payers and patients, especially for those living alone.